ASSESSMENT OF COLLECTION NURSERY OF WINTER GARLIC ON ECONOMY VALUABLE SIGNS - L. I. Gerasimova; A. F. Agafonov; Т. М. Seredin (Овощи России)
Garlic is one of the most ancient plants which the person turned to himself on advantage. The larger need for production of garlic for consumption and as raw materials for manufacture of medicinal preparations and, at last, just for use by the population as remedy for many diseases and for the preventive purposes led to the fact that bulk production of garlic in the world makes 24,836 million tons, and the area under garlic reached 1,465 million hectares. n Russia the area under garlic on all categories of farms is 28,4 thousand hectares, and production – 256,406 thousand tons. From factors influencing on the increase production of garlic, one of basic is a sort. Selection of garlic includes improvement of local grades, creation new high-yield, steady against diseases and to wreckers of grades, with the increased content of sugars, essential oils and biologically the active materials. Results of long-term researches by laboratory selection of onions cultures (VNIISSOK) on studying, assessment and selection exemplars grades of garlic winter, collected from different regions of Russia and the CIS countries, on a complex of signs are presented in article (winter hardiness, efficiency, to quality of production, resistance to wreckers and diseases).